2005
DOI: 10.1529/biophysj.104.047654
|View full text |Cite
|
Sign up to set email alerts
|

Collective Movement of Epithelial Cells on a Collagen Gel Substrate

Abstract: Collective cell movement acts as an efficient strategy in many physiological events, including wound healing, embryonic development, and morphogenesis. We found that epithelial cells (Madin-Darby canine kidney cell) migrated collectively along one direction on a collagen gel substrate. Time-lapse images of Madin-Darby canine kidney cells cultured on type-I collagen gels and glass substrates were captured by phase contrast microscopy equipped with an incubation system. On the gel substrate, the directions of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 29 publications
5
123
0
2
Order By: Relevance
“…Figure 5 shows the results of variation of the Young's modulus of the substrate. It can be seen that a stiffer substrate gives less attenuation of the signal and hence the cells feel the presence of the surrounding cells less, which is consistent with the experimental findings of Haga et al (2005) in epithelial cells cultured on collagen gel versus glass substrates. Therefore, the velocity of the cells decreases as the substrate becomes stiffer, a result which is supported by experiments of Lo et al (2000) who found that the speed of fibroblasts was 1.7 times greater on substrates with stiffness of E s = 140 kdyn/cm 2 with respect to their speed on substrates with E s = 300 kdyn/cm 2 .…”
Section: A Two-cell Problemsupporting
confidence: 87%
“…Figure 5 shows the results of variation of the Young's modulus of the substrate. It can be seen that a stiffer substrate gives less attenuation of the signal and hence the cells feel the presence of the surrounding cells less, which is consistent with the experimental findings of Haga et al (2005) in epithelial cells cultured on collagen gel versus glass substrates. Therefore, the velocity of the cells decreases as the substrate becomes stiffer, a result which is supported by experiments of Lo et al (2000) who found that the speed of fibroblasts was 1.7 times greater on substrates with stiffness of E s = 140 kdyn/cm 2 with respect to their speed on substrates with E s = 300 kdyn/cm 2 .…”
Section: A Two-cell Problemsupporting
confidence: 87%
“…In different situations, Haga et al (34) have observed that, on a soft collagen substrate, growing MDCK cell islands migrate collectively, driven by a fibroblast-like leader cell. It is striking to observe similar phenotypes in situations that are so different.…”
Section: Migration Triggered By a Model Wound And Advantages Of The Amentioning
confidence: 99%
“…To determine whether the movements of cells in our model are coordinated, we calculated the spatial correlation of the velocity C(r), given by (Haga et al 2005)…”
Section: Movement Of Epithelial Cells In the Model Is Coordinatedmentioning
confidence: 99%